A novel statin-mediated “prenylation block-and-release” assay provides insight into the membrane targeting mechanisms of small GTPases - Ali, Bassam R. (Academic Press, 2010)
Ras super-family small GTPases regulate diverse cellular processes such as vesicular transport and signal transduction. Critical to these activities is the ability of these proteins to target to specific intracellular membranes. To allow association with membranes Ras-related GTPases are post-translationally modified by covalent attachment of prenyl groups to conserved cysteine residues at or near their C-terminus. Here we used the HMG-CoA (3-hydroxy-3-methylglutaryl-coenzyme A) reductase (HMGCR) inhibitor mevastatin to develop a ‘prenylation block-and-release’ assay that allows membrane targeting of prenylated proteins to be visualized in living cells. Using this assay we investigated the cytosol to membrane targeting of several small GTPases to compartments of the secretory and endocytic pathways. We found that all Rabs tested were targeted directly to the membrane on which they reside at steady-state and not via an intermediate location as reported for Ras and Rho proteins. However, we observed that the kinetics of cytosol to membrane targeting differed for each Rab tested. Comparison of the mevastatin sensitivity and kinetics of membrane targeting of Rab23, Rab23 prenylation motif mutants and H-Ras revealed that these parameters are strongly dependent upon the prenyl transferase with Rab geranylgeranyl transferase substrates exhibiting higher sensitivity and requiring greater time to recover from mevastatin inhibition than farnesyl transferase substrates. We propose that this assay is a useful tool to investigate the kinetics, biological functions and the mechanisms of membrane targeting of prenylated proteins.